What’s in a name? - Mooney, E (Refugee Studies Centre, University of Oxford, 2012)
Over the past 25 years, Forced Migration Review and its precursor the Refugee Participation Network newsletter have not only captured, but arguably have also contributed to, important evolutions in the thinking and practice of approaches for protecting, assisting and finding solutions for forcibly uprooted people.